Maternal Nutritional Understanding, Attitudes, and Practices: Implications for Children’s Eating Habits - Vidhya C. S.; Sree, P. Narmatha; Rani , K. Sudha; Srivastava , Priya; Banu, A. M. Rashida; Sahu, Pratima; Rajpal , Charu (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2023)
Purpose: This study delves into the maternal understanding, attitudes, and practices related to nutrition and their potential implications for children's eating habits in India. Through a comprehensive examination, we aim to uncover valuable insights into the dynamics of maternal influence on children's dietary patterns in the specific cultural and contextual setting of India. The findings from this research contribute to a nuanced understanding of the interplay between maternal nutritional knowledge, attitudes, and practices, shedding light on potential avenues for targeted interventions to promote healthier eating habits among children in the Indian context. The structured questionnaire, encompassing dimensions of maternal nutritional knowledge, attitudes toward dietary practices, and specific behaviors influencing children's eating habits, serves as the primary tool for data collection. Anthropometric measurements of both mothers and children augment the dataset, offering a nuanced perspective on the nutritional status of participants. Limitations, such as reliance on self-reported data and the cross-sectional nature of the study, are acknowledged. Despite these constraints, this research aspires to contribute valuable insights into the intricate web of factors influencing children's eating habits within the unique socio-cultural landscape of India. The findings are expected to inform targeted interventions and policy recommendations, fostering healthier nutritional practices among children in this diverse and dynamic setting.